PHYSICO-GEOMETRIC INTERPRETATION OF MICROCUTTING TO DEVELOPMENT OF THE THEORETICAL THERMOMECHANICS OF GRINDING - Yury GUTSALENKO; Cătălin IANCU; Feodor NOVIKOV; Оlеg KLЕNОV (Fiabilitate şi Durabilitate)
A technical concept for the development of new technological solutions of the highperformance grinding with a significant increase in processing productivity under a slight increase in thermomechanical tension of the cutting process is proposed and considered. A conditional cutting stress is noted and considered among the factors of influence on the thermomechanics of grinding in research. The parametric structure of this factor accepted for consideration to a certain extent includes the angular characteristics of the geometry of the cutting grain and its friction with the material that is processed in. The implementation of the concept follows from the possibilities of a significant reduction in the conditional cutting stress and, correspondingly, the energy intensity of the treatment, which is consistent with practical data. Attention to the phase of elastic-plastic deformation without the formation of chips with the initial introduction of cutting grain into the processed material is drawn, and also at very small depths of intervention in the microcontacts between the cutting grain and object of processing too. The performed analysis is based on the previous author's development of the probabilistic approach to the formation of the maximum thickness of the cut. Analytical modeling is performed for conical and spherical models of cutting grain. The simulation results are compared, and recommendations on the application of the completed analytical development in further theoretical studies and calculations of technological projects of high-performance grinding operations are given.